A randomized study on the energy difference measured by electro photonic image on caregivers practiced Indian aesthetic dance and yoga - Hegde, Jayashree R.; Melukote, Sridhar K.; Vijayendra, Karuna; Singh, Deepeshwar (International Journal Of Community Medicine And Public Health, 2020)
Background: Electro photonic image (EPI) technique based on the bio-energy field, is growing as a novel technique in the fields of alternative medicine, conventional practices, psycho-physiology, psychology, and consciousness. In this study, the EPI instrument is used to assess emotional pressure which is termed as activation coefficient (AC), communication energy (C) level of various organ systems, and entropy (E) in the human energy field is assessed in the caregivers (CGs) of children with neurodevelopmental disorders (NDDs). Methods: Immediate effect of Indian aesthetic dance (n=31) and yoga (n=30) practices for 75 minutes were assessed in two randomized experimental groups that are later compared with the control group (n=30). The statistical analysis was done using IBM SPSS Version 21.0. Results: The activation coefficient of intervention groups showed a significant reduction in stress levels (p<0.001). Indian aesthetic dance intervention group showed significant improvement in the energy level of the organ systems namely respiratory, endocrine, musculoskeletal and digestive system (p<0.001); cardiovascular, nervous and immune systems (p<0.01) and yoga group in respiratory, musculoskeletal, nervous system (p<0.001); and cardiovascular, endocrine, and immune system (p<0.01). Both the intervention groups showed a significant reduction in entropy (p<0.001) post-intervention compared to the control group. Conclusions: The EPI parameters used for CGs of children with NDDs explore the possibility of using this instrument for measuring the bioenergy field that infers the health status of CGs before and after dance and yoga interventions.